HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA TENTANG PERTUMBUHAN GIGI DENGAN PERSISTENSI GIGI PADA ANAK BERKEBUTUHAN KHUSUS UMUR 6 - 12 TAHUN DI SEKOLAH LUAR BIASA NEGERI KOTABARU - Yuliana Nur Idzati; Siti Salamah; Metty Amperawati (Poltekkes Kemenkes Banjarmasin, 2021)
Many parents do not realize how important primary teeth are to their children, they think that primary teeth will be replaced and only permanent teeth need treatment. Tooth persistence is one of the dental and oral health problems where the primary teeth as a guide for the growth of permanent teeth do not fall out on time, while the replacement teeth have erupted. This study aims to determine the relationship between the level of parental knowledge about dental growth and dental persistence in children with special needs students aged 6 - 12 years at the Kotabaru State Special School. This type of research is an analytic study with a cross sectional design. Samples were taken using a total sampling technique of 74 samples at the Kotabaru State Special School. The analysis was carried out using the Chi-Square Test. The results showed that the knowledge of parents about tooth growth was mostly good and the persistence of teeth in children with special needs aged 6-12 years mostly did not have dental persistence. Based on the results of the Chi-Square statistical test, p-value > , it means that Ha is rejected. The conclusion of this study shows that there is no relationship between parental knowledge about tooth growth and dental persistence in children with special needs aged 6-12 years at the Kotabaru State Special School. Dental health workers are expected to cooperate with schools and parents so that a dental and oral nursing care program for children with special needs is expected. The role of parents is to maintain and increase more special attention for children with special needs who are in the period of child development.